DIODE LASER-INDUCED GUM ARABIC-G-ACRYLIC ACID - Sulaiman, Mohamed Gusm Alla Muhgoub (MATTER: International Journal of Science and Technology, 2019)
Aim of this study is to synthesis Gum Arabic-g- Acrylic acid using laser light as initiator to synthesis clean product that is free from any trace's chemicals substances. Firstly the graft of acrylic acid on Gum Arabic, initiated by (C.A.N), will be study under a nitrogen gas to get reaction conditions such as graft copolymerization temperature, reaction time, and Gum Arabic, monomer, and initiator concentrations. Percentage of graft efficiency (% GE) and percentage of graft yield (% GY) will be collocated. Graft copolymer will be recognized using FTIR Spectroscopy, (TGA) analysis, (XRD) diffraction and (SEM) microscope. The graft will be later used in drug delivery carrier to control cancer in brain and matrices for colon aiming medicine delivery systems. This study focused to new trends and latest developments in this area where laser light was found to be efficient and clean method for synthesis GA-g-Acrylic Acid.